Unfairness and Structural Injustice in a Middle School in Aotearoa - Moreton, Brian (Auckland University of Technology, 2021)
This research commenced with an observation that unfairness/injustice encountered in a well-resourced school may be different from that experienced in a school challenged with behavioural concerns and academic underachievement. Part of this difference may be due to pedagogical, cultural unresponsiveness of the school towards the Māori and Pasifika participants; that is, relational cultural values. Alternatively, there could be other reasons entirely. The thesis represents my personal growth in moving from a psychological/scientific view, that all could be found by applying the right instruments to the people in question, to a view that the responses and people needed to be seen in a political and social context. It represents an original contribution to critical psychology. One way of finding out about unfairness/injustice is to ask students for their perceptions. Subsequently, I searched the literature for what it could reveal regarding student perspectives on unfairness. The literature proved to be mostly silent on the topic. I attributed the silence to the influence of a distributive justice paradigm and its associated metaphors. To rectify this literature gap, and reveal the students’ voice, I proposed two empirical inquiries and a critical reinterpretation of the data from the empirical findings. These research undertakings are aimed at opening the gap in the literature to enable these voices to be heard. The first empirical activity involved an innovative qualitative survey using a purposive sample of 77 early adolescents, middle school participants to determine the diversity of a phenomenon of experienced unfairness. The second empirical activity inquired into the processes behind assigning meaning to unfairness and involved interviewing 13 students. Finally, I explored injustice at a whole school level by a critical reinterpretation of the data focusing on cultural, structural injustices. The first interpretive activity was to analyse the survey data, using thematic analysis, in order to establish the diversity of unfairness within this student population. The second stage involved an analysis of data from 12 semi-structured interviews using interpretive phenomenological analysis, with a focus on the processes in assigning meaning to unfairness. The combined data revealed the possibility of a phenomenon of perceived unfairness as a judgment of accountability for unfairness (an adverse event, culpability being established for that event, and a comparison of the event against a breach of ethical standards, via counterfactual cognitive processes). This interpretation revealed four superordinate themes of: ‘Why did she do that to me?’; ‘It is not fair!’; ‘Intense relational emotions’; and, ‘Managing intense emotion.’ A third activity involved a critical reinterpretation of the unfairness themes as structural injustices resulting from unequal cultural, relational power. The structures were theorised as the result of a mutual conditioning process of neoliberal school culture and student cultural values. Students’ Māori and Pasifika cultural, interpersonal, relational values provide the basis for the students’ counter-conditioning. The neoliberal influenced culture was evaluated through the Education Review Office reports and the technical processes of performativity, managerialism, and competition. The students’ counter-conditioning was through judgements of injustice. Mutual conditioning produced four structural injustices based on violations of Pasifika and Māori cultural, relational values. Four structures were analysed in the form of underachievement, intra-peer bullying as lateral violence, teacher bullying, and the closure of the participants’ intermediate school. I argue that counterconditioning contributed to students’ marginalisation by maintaining their underachievement, disrupting the establishment of strong learner identity, silencing and stigmatising, and continuing colonial trauma. Teacher bullying was disrupting the development of a model of a successful teacher-student learning partnership. A judgment of either individual judgement of unfairness or collective structural injustice may generate a ‘force’ of relational power from the embedded cognition of these judgements. Through emotional complexes, theorised as a social relational power, bodily euphoria as anger can affect a range of strategic action. Anger may be associated with strategic disengagement as resistance, but inadvertently contribute to marginalisation by withdrawal. Sadness, as dysphoria, may contribute to engagement coping skills. The utterance of “It is not fair” may be a protest and a warning of cultural, relational injustice.
Keywords: Unfairness; Structural injustice; New Zealand middle school; Cultural unresponsiveness